Pelatihan Da’iyah Majelis Ulama Indonesia - Ismail Nasution; Enni Efrida Nasution (Yayasan Perguruan Kampus, 2025)
The Indonesian Ulema Council's Da'iyah Training is a strategic effort to improve the competence and capacity of Da'iyah (Islamic preachers) in carrying out their da'wah duties professionally and effectively. This training activity is designed to equip Da'iyah with in-depth religious knowledge, persuasive communication skills, and managerial skills that support the implementation of da'wah in various levels of society. In the training, participants receive material on the principles of da'wah, engaging delivery techniques, the use of modern da'wah media, and strengthening the character and ethics of da'is in accordance with Islamic values. The training process is conducted through interactive methods, group discussions, simulations, and case studies to optimally enhance participant understanding and engagement. In addition to technical aspects, this training also emphasizes the importance of adapting da'wah in the digital era by utilizing information technology and social media as a means of disseminating da'wah messages. This is crucial considering the highly dynamic and complex challenges of da'wah in the modern era. Training evaluations show a significant increase in participants' abilities to deliver da'wah in a more systematic, engaging, and contextual manner. By improving the quality of Da'iyah, it is hoped that their contribution to building a society with noble morals, tolerance, and harmony can be realized. Overall, this training by the Indonesian Da'iyah Council has had a positive impact in strengthening the role of Da'iyah as agents of social and spiritual change in Indonesia.